Oleophobic composite films based on multi-layer graphitic scaffolding - Michael Warwick (New Journal of Chemistry, 2021)
A new oleophobic composite material synthesised by utilising plasma-exfoliated multi-layered graphitic (MLG) material as scaffolding is presented herein. The composite consisted of a polyelectrolyte/fluorosurfactant complex derived from polydiallyldimethylammonium chloride (PDDA) and sodium perfluorooctanoate (PFO) and was used to prepare free-standing MLG composite films.